Maturity evaluation in project management and implementation of a PMO case study - Ferreira, H. (2016)
As a collaborator of MCG and actively participating in many of the company's projects, I often find myself with preventable situations, ones more complex than others, that call into question the success of projects. After the conclusion of my training in project management (PM), it became clear that many of these problems are easily surmountable through correct application of tools and techniques in PM. Being MCG a successful company in continuous growth since 2011, the introduction of a Project Management Office can optimize and contribute to the improvement of its results by reducing unplanned work and reducing costs through risk management, thus introducing a PM culture in the company. The aim is to make a diagnosis of the maturity in project management, identify the main obstacles to the implementation of a PMO, sensitize project teams for the importance of PM and on that basis, it is suggested to use the unanimously recognized techniques and tools. In addition to the internal knowledge already pre-purchased in the company, a maturity assessment was carried out in PM using an adaptation of the OPM3 model, recommended by the Project Management Institute (PMI). Simultaneously, during the application of the model, formal conversations with responsible for the PM of different units were held. Despite the constraints encountered, such as the inability to assess accurately the costs associated with each of the projects, this evaluation has shown that maturity in PM in the organization is still below the expectations for a company with the size and the market position as MCG. Therefore, it is recommended to create a PMO in order to standardize procedures, tools and techniques throughout the company, thus contributing to increase the project management culture in all employees.